2007
DOI: 10.1111/j.1399-6576.2007.01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of withdrawal movement associated with injection of rocuronium in children: comparison of remifentanil, alfentanil and fentanyl

Abstract: Remifentanil, alfentanil and fentanyl all reduced the incidence of withdrawal movement when administered 90 s before the injection of rocuronium compared with saline. Remifentanil was the most effective, followed by alfentanil. Fentanyl was less effective but significantly different from the saline in reducing withdrawal movement in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 13 publications
0
25
0
Order By: Relevance
“…Pain upon intravenous infusion has been reported, though premedication with analgesics have been studied, and fentanyl was noted to decrease pain responses in one study. 34 Optimal dosing to maximize the number of completely paralyzed patients, provide quick onset of action, and minimize duration of paralysis in the neonatal and infant populations requires further investigation.…”
Section: Drug Of Choicementioning
confidence: 99%
“…Pain upon intravenous infusion has been reported, though premedication with analgesics have been studied, and fentanyl was noted to decrease pain responses in one study. 34 Optimal dosing to maximize the number of completely paralyzed patients, provide quick onset of action, and minimize duration of paralysis in the neonatal and infant populations requires further investigation.…”
Section: Drug Of Choicementioning
confidence: 99%
“…Besides lidocaine, several other drugs such as ondansetron [8,9], magnesium sulfate [10], sodium bicarbonate [10,15], fentanyl [16,17], and remifentanil [18,19] are effective in reducing pain on rocuronium injection, but pretreatment of lidocaine or other drugs before rocuronium prolongs the time between anesthesia induction and neuromuscular block administration. In addition, most of these drugs can, even in rare cases, induce adverse effects such as allergic reaction, bradycardia, and hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…cannula. Withdrawal movements were observed by the same blinded investigator using a 4-point scale: 0 = no movement; 1 = movement limited to the wrist; 2 = movement limited to the arm; and 3 = generalized movement [2,6]. A grade of 2 or more was considered significant movements.…”
Section: Methodsmentioning
confidence: 99%
“…It has a rapid onset and an ultra-short duration of action with a stable, short context-sensitive half-time [5]. Many studies have reported that remifentanil effectively reduces rocuronium-induced pain and withdrawal movements [6,7,8,9]. There have recently been studies on the EC 50 and EC 95 of remifentanil to prevent withdrawal movements in adults [4,10] and children [10] using the Dixon up-and-down method and by probit analysis.…”
Section: Introductionmentioning
confidence: 99%